2020
DOI: 10.1371/journal.pone.0244741
|View full text |Cite
|
Sign up to set email alerts
|

Three new species of Levinsenia Mesnil, 1897 (Annelida: Paraonidae) from shallow and deep waters of Southwestern Atlantic Ocean

Abstract: Three new species of Levinsenia were collected during a benthic survey, from 10–3,000 m deep, in Espírito Santo Basin, off the southeastern Brazilian coast. These species are L. paivai sp. nov., L. blakei sp. nov. and L. lesliae sp. nov. Members of L. paivai sp. nov. are recognized by the presence of nine pairs of well-developed and heavily ciliated branchiae, those of L. blakei sp. nov. are characterized by the presence of three pairs of small branchiae, and those of L. lesliae sp. nov., by the absence of bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In this study, the use of the methyl green stain has not shown to be a decisive tool for the identification of morphological characters, as none of the described species showed a well-marked colour pattern among the specimens ( S1 Fig ). Several studies have pointed to methyl green staining as a very useful tool for taxonomic identification of different families of polychaetes, such as Capitellidae, Cirratulidae, Paraonidae, Sabellidae and Spionidae [ 39 – 41 ]. However, the use of this technique for taxonomy requires standard methodological procedures, for example, the time of exposure to MG, the concentration of the MG solution, and washing times to remove excess MG, so we can be sure that the patterns found in each species or group do not differ due to differences in the methodologies applied for staining.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the use of the methyl green stain has not shown to be a decisive tool for the identification of morphological characters, as none of the described species showed a well-marked colour pattern among the specimens ( S1 Fig ). Several studies have pointed to methyl green staining as a very useful tool for taxonomic identification of different families of polychaetes, such as Capitellidae, Cirratulidae, Paraonidae, Sabellidae and Spionidae [ 39 – 41 ]. However, the use of this technique for taxonomy requires standard methodological procedures, for example, the time of exposure to MG, the concentration of the MG solution, and washing times to remove excess MG, so we can be sure that the patterns found in each species or group do not differ due to differences in the methodologies applied for staining.…”
Section: Discussionmentioning
confidence: 99%